The use of remote sensing to detect the change in land use by date palms cultivation in Baghdad governorate - Amad Kadhim, Sherin; Hassan Kadhim, Dalal (Al-Adab Journal, 2021)
The research aims to reveal spatial variation and temporal change in land use by date palms cultivation in Baghdad governorate for the period between 2001 and 2018, Using satellite images recorded by the ETM sensor carried by the US Landsat-7 satellite and the OLI sensor carried by the Landsat-8 satellite. A series of steps were carried out, starting with the engineering and radiometric corrections, enhancement operations, super and a super classification, based on the classification of Anderson and others (USGS) to classify land use and land cover. Procedure for the change detection in date palms cultivation for the period between 2001 and 2018 using equation of absolute change and relative change. As well as making and distributing a questionnaire form containing 500 questionnaires and field studies to fill the shortage of data and information about the study area.The study found a set of results, the most prominent of which was the existence of a negative change in the areas of land use by cultivating date palms during the period (2001-2018), at a rate of (-16.8) % in Baghdad governorate, and at different rates in all districts of Baghdad governorate. Al-Sadr district came at the forefront of the districts in terms of the rate of change of the area, which amounted to (-1OO) %, while Al-Mada'in district ranked last with a change rate of (-3) % of the total area of ​​palm trees.